2001
DOI: 10.1039/b100022p
|View full text |Cite
|
Sign up to set email alerts
|

A switchable salicylaldimine-based achiral bent-shaped mesogen: synthesis and characterization

Abstract: The first achiral bent core banana-shaped mesogen consisting of a thermally and hydrolytically stable salicylaldimine (2-hydroxybenzylideneamine) mesogenic segment has been synthesized and evaluated for its liquid crystalline behavior. This novel compound exhibits a single switchable mesophase over 60 uC temperature range. The textural and electro-optic switching characteristics suggest that the phase could be of the antiferroelectric type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…The synthesis of compound II is described in our earlier publication [8]; compound I was prepared in a similar way and details will be published elsewhere. Briefly a mixture of 3-(4-aminobenzoyloxy)phenyl 4-aminobenzoate, either 2-hydroxy-4-n-hexyloxybenzaldehyde or 2-hydroxy-4-ndecyloxybenzaldehyde, absolute ethanol and a trace of acetic acid were heated to reflux until the solid compounds I and II precipitated out, respectively.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of compound II is described in our earlier publication [8]; compound I was prepared in a similar way and details will be published elsewhere. Briefly a mixture of 3-(4-aminobenzoyloxy)phenyl 4-aminobenzoate, either 2-hydroxy-4-n-hexyloxybenzaldehyde or 2-hydroxy-4-ndecyloxybenzaldehyde, absolute ethanol and a trace of acetic acid were heated to reflux until the solid compounds I and II precipitated out, respectively.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Since the low to high temperature crystal transition splits into a doublet under pressure as described in the later sections, the first transition of the pure sample seems to be composed of the Cr 3 -Cr 2 and Cr 2 -Cr 1 transitions, but these crystalline phases appear neither on cooling from the isotropic liquid nor in subsequent heating runs. The B 2 phase of this compound is identified using electro-optic switching and X-ray studies [8]. The thermodynamic quantities associated with the phase transitions for the two compounds are listed in the table.…”
Section: Dta Measurements Under Pressurementioning
confidence: 99%
“…[11] An attractive feature of this compound over other bent-core mesogens is that it exhibits a switchable B 2 phase over a very large temperature range 60°C, and the textural and electro-optic switching characteristics confirms its antiferroelectric behaviour. [11] Krishna Prasad et al [8] were the first to investigate the phase behaviour of PHDBB compound under hydrostatic pressures up to 300 MPa using high-pressure differential thermal analysis and light transmission methods. They observed that the temperature range of the B 2 phase remains unaltered (~57°C) over the entire range of pressure.…”
Section: Introductionmentioning
confidence: 88%
“…In order to investigate the dynamics of the polarization switching behavior, the switching currents of mixture 80C/20D were measured with an applied square wave field (as Vpp ¼ 150 V, f ¼ 10 Hz) in the SmC* phase. The switching current curves of mixture 80C/20D at 100 C are shown in Figure 5 reversal (Yelamaggad and Hiremath 2001). The switching time as a function of the temperature is shown in Figure 5(b), with the same field and frequency (i.e., Vpp ¼ 150 V, f ¼ 10 Hz).…”
Section: Electro-optical Behaviormentioning
confidence: 99%